2016
DOI: 10.1063/1.4958946
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and magnetism of Mn-doped GaSb for spintronic applications: A DFT study

Abstract: We have carried out first-principles spin polarized calculations to obtain comprehensive information regarding the structural, magnetic, and electronic properties of the Mn-doped GaSb compound with dopant concentrations: x = 0.062, 0.083, 0.125, 0.25, and 0.50. The plane-wave pseudopotential method was used in order to calculate total energies and electronic structures. It was found that the MnGa substitution is the most stable configuration with a formation energy of ∼1.60 eV/Mn-atom. The calculated density o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…A large positive J value (such as 23.9 meV of (0, 6) configuration) indicates a strong FM spin exchange coupling of the Mn–Mn pair, which may lead to a high coercivity. The Curie temperature T C can be roughly estimated by means of the mean-field approximation and calculated according to the following equation [ 50 ]: where Δ E is the total energy difference between AFM and FM states and k B is the Boltzmann constant. Using Equation (2), the T C of (0, 1), (0, 6), (0, 8) and (0, 11) configurations are estimated to be higher than the room temperature; especially, the T C of (0, 6) configuration is up to 2951 K. Such high Curie temperatures make the material promising for practical applications.…”
Section: Resultsmentioning
confidence: 99%
“…A large positive J value (such as 23.9 meV of (0, 6) configuration) indicates a strong FM spin exchange coupling of the Mn–Mn pair, which may lead to a high coercivity. The Curie temperature T C can be roughly estimated by means of the mean-field approximation and calculated according to the following equation [ 50 ]: where Δ E is the total energy difference between AFM and FM states and k B is the Boltzmann constant. Using Equation (2), the T C of (0, 1), (0, 6), (0, 8) and (0, 11) configurations are estimated to be higher than the room temperature; especially, the T C of (0, 6) configuration is up to 2951 K. Such high Curie temperatures make the material promising for practical applications.…”
Section: Resultsmentioning
confidence: 99%
“…Our results show that magnetic atoms tend to be ferromagnetic coupled, as shown in Table 1, the most stable configuration of ferromagnetism is the (0, 10) configuration with ∆E FM −244.3 meV. In the experiment, the influence of the structure for the company and magnetic doping SiC film was studied by Sun et al [39], and they found that when the annealing temperature rose to 1200 • C, the doping atom Co formed the compound complete CoSi, and the magnetic film results showed that all films exhibit intrinsic ferromagnetism at 300 K. In order to evaluate the intensity of FM magnetic coupling, the T C is roughly estimated by the mean-field approximation method of total energy difference ∆E FM = E FM −E AFM , and calculated by the following formula [40,41]:…”
Section: (Cr Co)-codoped 4h-sicmentioning
confidence: 99%
“…[18,19] Recently, we have identified several half-metallic materials by using transition metal elements to dope group III-V binary semiconductors. [20][21][22][23][24] Sezã et al [25] investigated Mn-doped GaSb using the density functional theory method and found that the doped material has FM halfmetallic properties. On the other hand, magnetic half-metallic materials made by doping have better compatibility compared with semiconductors and have shown high research and application value, so the research on this type of half-metallic materials have attracted increasing attention.…”
Section: Introductionmentioning
confidence: 99%